The Influence of Organizational Learning, Job Stress, and Employee Recognition on Employee Performance at PT. Socfindo Tanah Gambus Gardens - Firmauli Valentina Siregar; Kartini Harahap (PT FORMOSA CENDEKIA GLOBAL, 2023)
This research aims to determine the effect of organizational learning, work stress and employee recognition on employee performance at PT. SOCFINDO Kebun Tanah Gambus. The influence of organizational learning, work stress and employee recognition will be analyzed partially and simultaneously on employee performance. The form of research used in this research is quantitative research with an associative approach. Sampling was carried out using a purposive sampling technique and used 89 respondents as samples. The results of this research show that the variables of organizational learning, work stress, and employee recognition have a positive and significant effect both partially and jointly (simultaneously) on employee performance. The coefficient of determination test shows that there is a fairly close relationship between organizational learning, work stress and employee recognition on employee performance with an R value of 0.886.